2008
DOI: 10.1002/prot.22302
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pressure on helix‐coil transition of an alanine‐based peptide: An FTIR study

Abstract: Effects of pressure and temperature on the helix-coil transition of an alanine-based peptide (Ac- AA(AAKAA)(3)AAY-NH(2)) have been investigated using CD and FTIR spectroscopy. From the correlation between CD and FTIR data, we showed that the change in infrared intensity of the amide I' band at 1633 cm(-1) is almost identical to the change in the helical content calculated from the CD result. Thus, we monitored the amide I' band intensity at 1633 cm(-1) to determine the helical content at high pressures. We det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
48
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(55 citation statements)
references
References 34 publications
7
48
0
Order By: Relevance
“…The volume decrease upon helix formation observed in TTET experiments is in agreement with FTIR studies on Ala-based peptides, which also observed a stabilization of the helical state (17). Using an equilibrium linear Ising model to analyze the FTIR data yielded a reaction volume of −0.98 ± 0.04 cm 3 /mol per residue, which is larger than the reaction volume of −0.23 cm 3 /mol per residue determined by TTET (Fig.…”
Section: Effect Of Pressure On the Elementary Rate Constants For Helisupporting
confidence: 87%
See 1 more Smart Citation
“…The volume decrease upon helix formation observed in TTET experiments is in agreement with FTIR studies on Ala-based peptides, which also observed a stabilization of the helical state (17). Using an equilibrium linear Ising model to analyze the FTIR data yielded a reaction volume of −0.98 ± 0.04 cm 3 /mol per residue, which is larger than the reaction volume of −0.23 cm 3 /mol per residue determined by TTET (Fig.…”
Section: Effect Of Pressure On the Elementary Rate Constants For Helisupporting
confidence: 87%
“…Thus, addition or removal of a helical residue proceeds through a transitory high-energy state with a large volume, possibly due to the presence of unsatisfied hydrogen bonds, although steric effects may also be involved. volume of the helical state compared with the unfolded state (17). Molecular dynamics simulations, in contrast, suggested that the unfolded state of Ala-based peptides has a slightly smaller volume than the helical state (18).…”
Section: Significancementioning
confidence: 88%
“…Below we focus on the Zimm-Bragg model, as this has been used to characterize the experimental data. 14,15 In particular, the elongation parameter s corresponds to the equilibrium constant for adding a single helical hydrogen bond.…”
Section: Resultsmentioning
confidence: 99%
“…The same model was fitted to the data for RT ln s(P, T) reported by Imamura et al, based on FTIR measurements. 14 The fits to the raw data are shown in Fig. S2 of the supplementary material.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation